BUDGETING AS A CONTROL SYSTEM IN FINANCIAL AND CREDIT ACTIVITIES - Levandivskyi , O.T.; Balaniuk , I. F.; Matkovsky , P. Ye.; Shelenko , D. I. (The actual problems of regional economy development, 2022)
The article considers budgeting as a system of control over the activities of financial institutions. Emphasis is placed on the need to introduce budgeting in the activities of financial institutions. Methodical approaches in budgeting of financial and credit institutions are considered and analyzed. The role of budgeting in the activities of financial institutions based on the functions of budget planning, organization, motivation, control and regulation is reflected. An analysis of the factors influencing the low efficiency of budgeting in the activities of financial institutions. The main types of budget assessment depending on the purpose and methods of its implementation are studied. Emphasis is placed on the feasibility of analyzing the budget of the financial institution as a plan for future operations integrated into the technologies formed in accounting and financial planning. It was found that the basis of any budgeting of financial institutions are financial flows, financial risks, key indicators of the financial market, profits and structural components, the amount of required funds and reserves, currency position, etc. At the heart of the budgeting system are scientifically sound principles that clearly define the nature and content of budgeting, creating conditions for effective work and reducing the possibility of negative factors, namely: the principle of unity; the principle of completeness; principle of accuracy; the principle of participation, coordination and responsibility. The advantages and disadvantages of the main options for budgeting in financial institutions are identified. The stages and modern methods of budgeting are specified.Attention is paid to the relationship between the structural units of the financial institution for budgeting. It is proved that budgeting is one of the most effective tools for finding internal reserves in the activities of financial institutions. Allows you to plan revenues and expenses and as a result implement the concept of "exception management". This concept is a way of organizing management, in which based on the implementation of the planning function through the budget system, further management influence, motivation and control is carried out through the implementation of the analytical function in assessing deviations from planned budget options.